A collaborative cervical precancer screening strategy with concurrent HPV genotyping and visual inspection using alumni of a training centre across Ghana: The Rotary ‘Protect Your Pearl’ initiative - Kofi Effah; Dorothy Letitia Ametefe; Joseph Emmanuel Amuah; Nana Owusu Mensah Essel; Maxwell Afetor; Annita Edinam Dugbazah; Emmanuel Deho; Seyram Kemawor; Stephen Danyo; Edna Sesenu; Georgina Tay; Yohane Teye Kitcher; et al. (PLoS ONE, 2026)
Background Cervical cancer is a leading cause of cancer mortality among Ghanaian women, yet screening uptake is under 5%. The Cervical Cancer Prevention and Training Centre (CCPTC) partnered with Rotary Clubs across the country to implement the first-ever nationally representative cervical precancer screening project and to demonstrate the feasibility of an integrated nationwide screening program. Methods We conducted a cross-sectional analysis of 1,636 asymptomatic women aged 25 years and above screened at 29 government and private facilities across all 16 regions of Ghana (January–February 2025). Eligible women underwent concurrent hr-HPV genotyping (Sansure MA-6000 platform) and VIA by CCPTC-trained alumni, with immediate thermal ablation for eligible VIA-positive lesions (TZ type 1 or 2). Multivariable logistic regression (backward stepwise elimination, P < 0.25 retention threshold) identified factors associated with hr-HPV positivity and VIA positivity. Analyses were performed in Stata v17.0. Results Among 1,636 women, the overall hr-HPV prevalence was 26·6% (95% CI, 24·5–28·8) and the VIA ‘positivity’ was 4·0% (95% CI, 3·1–5·0). Predominant genotypes were HPV52 (5·3%), HPV58 (4·4%), and HPV51 (3·6%); HPV16 and HPV18 together accounted for <5% of infections. Independent factors associated with hr-HPV infection were HIV infection (aOR=5·77; 95% CI, 2·07–16·13, P = 0.001) and having a steady partner (aOR=2·02; 95% CI, 1·22–3·36, P = 0.006); being married/cohabiting (aOR=0·51; 95% CI, 0·38–0·69, P < 0.001) or widowed (aOR=0·43; 95% CI, 0·23–0·82, P = 0.011), and prior screening (aOR=0·67; 95% CI, 0·48–0·92, P = 0.014) were protective. VIA ‘positivity’ was independently associated with HIV infection (aOR 7.49, 95% CI 1.99–28.19, P = 0.003). Regional hr-HPV prevalence varied from 10·0% to 39·2%. Thirty-five percent of VIA-positive women received same-visit thermal ablation. Conclusion This decentralized alumni-driven model integrating off-site HPV testing, task-shifted VIA, and immediate thermal ablation proved operationally feasible across Ghana’s diverse health system and revealed a substantial hr-HPV burden. The approach offers a scalable blueprint for national cervical cancer control and informs Ghana’s transition toward HPV-based screening.